Busca de sentido para a existência em peregrinos a Santiago de Compostela - Carunchio, Beatriz Ferrara (2011)
This master study aimed to investigate the search for meaning in people who had made a pilgrimage on the Way of St. James. For this, beside literature research, we also made an empiric research. We developed a questionnaire based on interviews and testimonies collected by us. Subsequently, the questionnaires were tabulated and analyzed. We concluded that the Way of St. James is not only a Catholic route, not just a religious route. It includes numerous speeches and values, religious and secular. This allows the pilgrim to contact himself, enabling considerations and questions about himself, his life and the reality which the pilgrim belongs to. So it makes possible the construction of a new meaning for his own life